The dynamics and mediating factors of students’ emotional and social engagement in a project-based writing course - Li, Jingya; Chen, Mo; Zheng, Qun (System (Linköping), 2024)
Studies of student engagement in language learning have burgeoned in the last three decades. However, its dynamic trajectory and the attendant mediating factors leading to various outcomes in project-based language learning (PBLL) have been underexplored. PBLL emphasizes social communication and engagement as students complete complex tasks over an extended period of time, making it distinct from traditional teacher-centered instruction. With this focus in mind, our study draws on Complexity of Dynamic Systems Theory (CDST) to examine the longitudinal development of emotional and social engagement among Chinese EFL students in an English for Academic Purposes (EAP) writing course, and to explore factors accounting for possible changes in those two types of engagement. Using three sets of questionnaires to track student engagement over the course of a learning project, we found an overall increase of emotional and social engagement during students’ learning process, despite a slight dip at the midway point. A follow-up interview showed that engagement changes were mainly driven by peer influence, task completion in PBLL, leadership, and preference for PBLL. These findings provide insight into the dynamics of student engagement in PBLL settings in China and have implications for EAP writing pedagogy.